AN EMPIRICAL ANALYSIS TO SUPPORT THE DETERMINATION OF THE RIGHT FEE IN BATHING CONCESSIONS - Pierluigi Morano; Leonardo Damiani; Paola Amoruso; Debora Anelli; Felicia Di Liddo; Francesco Tajani (Valori e Valutazioni)
The use of the public State-owned lands for privately managed bathing establishments involves the payment of a properly agreed concession fee and the definition of its duration. On these aspects, Italy appears not to be in line with the current European legislation and therefore an update of the current legal provisions presupposes an investigation to identify the existence and the extent of the imbalances between the paid fee and the real revenues of the bathing activities. Starting from an overview of the international and national regulations on the topic of the bathing concessions, the research intends to provide an empirical analysis of existing gaps between the annual concession fee currently paid by the private operator and the annual revenues deriving from the bathing activity of each facility, for supporting the public administrations in determining the fair bathing concession fee to be paid to the State domain. With reference to a sample of bathing establishment located in the Apulia region (southern Italy) randomly selected through a web survey, the first results are provided and discussed.